A SIMPLIFIED INVENTORY CLASSIFICATION APPROACH: COMBINING MULTIPLE CRITERIA USING THE BORDA METHOD (Third Sector Social Economic Review, 2024)
Traditional inventory classification approaches, such as ABC (Always Better Control), VED (Vital-Essential-Desirable), and their matrix forms, typically account for a limited range of inventory characteristics. Techniques like multi-criteria decision analysis, linear programming, and heuristic algorithms, which can consider more characteristics, require technical knowledge and expertise. However, the majority of small and medium-sized enterprises (SMEs) lack the staff capable of applying these methods. Therefore, a method that can accommodate numerous characteristics and is easy to use is necessary. This paper introduces a classification approach that combines multiple inventory characteristics using the BORDA method, specifically designed to assist SME managers with limited technical expertise. A dataset containing 47 stock keeping units (SKUs), including the average cost, annual cost, and lead time characteristics, is used to demonstrate the application of the proposed approach. The implementation reveals that the BORDA method provides a comprehensive and unbiased solution to inventory classification by systematically combining the rankings of various inventory characteristics. This approach simplifies the classification process by integrating multiple characteristics in a straightforward manner, making it particularly suitable for SMEs.
Keywords: SMEs; Inventory management; Inventory classification; BORDA method; Rank correlation